2003
DOI: 10.5551/jat.10.253
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Wave Velocity in Lower-Limb Arteries among Diabetic Patients with Peripheral Arterial Disease.

Abstract: Objective: Patients with type 2 diabetes mellitus are at an increased risk of atherosclerosis including peripheral arterial disease (PAD). The purpose of this study was to examine the possible alteration in pulse wave velocity (PWV) in lower-limb arteries among diabetic patients with PAD. Methods: We measured brachial-ankle PWV (baPWV) using an automatic device in 101 healthy control subjects and 102 type 2 diabetic patients including those with PAD. Results: Diabetic patients without PAD showed a higher baPWV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 21 publications
3
87
0
1
Order By: Relevance
“…In light of the BP dependency of arterial stiffness, in the presence of hemodynamically relevant lower limb artery stenosis, the measure of PWV loses its significance as a measure of stiffness. 26 In this present study, as normally observed, limb PWV was higher than aortic PWV, and inclusion criteria required the absence of hemodynamically significant lower limb occlusive lesions.…”
Section: Discussionmentioning
confidence: 67%
“…In light of the BP dependency of arterial stiffness, in the presence of hemodynamically relevant lower limb artery stenosis, the measure of PWV loses its significance as a measure of stiffness. 26 In this present study, as normally observed, limb PWV was higher than aortic PWV, and inclusion criteria required the absence of hemodynamically significant lower limb occlusive lesions.…”
Section: Discussionmentioning
confidence: 67%
“…The bPEP and bET were measured using an ABI-form device, which automatically and simultaneously measures blood pressures in both arms and ankles using an oscillometric method. [7][8][9] Occlusion and monitoring cuffs were placed tightly around the upper arm without blood access and both sides of the lower extremities in the supine position. The bET was automatically measured from the foot to the dicrotic notch (equivalent to the incisure on the downstroke of the aortic pressure wave contour produced by the closure of the aortic valve) of the pulse volume waveform.…”
Section: Assessment Of Bpep Bet Abi and Brachial-ankle Pulse Wave Vmentioning
confidence: 99%
“…The values of ABI and brachial-ankle pulse wave velocity were also measured, and the measurement method has been reported and validated in earlier studies. [7][8][9] Collection of demographic, medical and laboratory data Demographic and medical data, including age, gender, smoking history (ever vs. never) and comorbid conditions, were obtained from medical records and interviews with patients. The body mass index was calculated as the ratio of weight in kilograms divided by the square of height in meters.…”
Section: Assessment Of Bpep Bet Abi and Brachial-ankle Pulse Wave Vmentioning
confidence: 99%
“…16,17 For measuring baPWV, pulse waves that were obtained from the brachial and tibial arteries were recorded simultaneously, and the transmission time, which was defined as the time interval between the initial increase in brachial and tibial waveforms, was determined. The transmission distance from the arm to each ankle was calculated according to body height.…”
Section: Assessment Of Bapwv Rbpep and Rbetmentioning
confidence: 99%